Simplifying
-2p^{2} + 28p + -66 = 0
Reorder the terms:
-66 + 28p + -2p^{2} = 0
Solving
-66 + 28p + -2p^{2} = 0
Solving for variable 'p'.
Factor out the Greatest Common Factor (GCF), '2'.
2(-33 + 14p + -1p^{2}) = 0
Factor a trinomial.
2((-11 + p)(3 + -1p)) = 0
Ignore the factor 2.
#### Subproblem 1

Set the factor '(-11 + p)' equal to zero and attempt to solve:
Simplifying
-11 + p = 0
Solving
-11 + p = 0
Move all terms containing p to the left, all other terms to the right.
Add '11' to each side of the equation.
-11 + 11 + p = 0 + 11
Combine like terms: -11 + 11 = 0
0 + p = 0 + 11
p = 0 + 11
Combine like terms: 0 + 11 = 11
p = 11
Simplifying
p = 11
#### Subproblem 2

Set the factor '(3 + -1p)' equal to zero and attempt to solve:
Simplifying
3 + -1p = 0
Solving
3 + -1p = 0
Move all terms containing p to the left, all other terms to the right.
Add '-3' to each side of the equation.
3 + -3 + -1p = 0 + -3
Combine like terms: 3 + -3 = 0
0 + -1p = 0 + -3
-1p = 0 + -3
Combine like terms: 0 + -3 = -3
-1p = -3
Divide each side by '-1'.
p = 3
Simplifying
p = 3#### Solution

p = {11, 3}